Aldosterone-Regulating Receptors and Aldosterone-Driver Somatic Mutations - Lim, Jung Soo; Plaska, Samuel W.; Rege, Juilee; Rainey, William E.; Turcu, Adina F. (Frontiers in Endocrinology, 2021)
Background Somatic gene mutations that facilitate inappropriate intracellular calcium entrance have been identified in most aldosterone-producing adenomas (APAs). Studies suggest that angiotensin II and adrenocorticotropic hormone (ACTH) augment aldosterone production from APAs. Little is known, however, regarding possible variations in response to hormonal stimuli between APAs with different aldosterone-driver mutations. Objective To analyze the transcript expression of type 1 angiotensin II receptors (AGTR1), ACTH receptors (MC2R), and melanocortin 2 receptor accessory protein (MRAP) in APAs with known aldosterone-driver somatic mutations. Methods RNA was isolated from APAs with mutations in: KCNJ5 (n = 14), ATP1A1 (n = 14), CACNA1D (n = 14), and ATP2B3 (n = 5), and from normal adjacent adrenal tissue (n = 45). Transcript expression of MC2R, MRAP, AGTR1, aldosterone synthase (CYP11B2), 17α-hydroxylase/17,20-lyase (CYP17A1), and 11β-hydroxylase (CYP11B1) were quantified using quantitative RT-PCR and normalized to β-actin. Results Compared to adjacent normal adrenal tissue, APAs had higher transcript levels of CYP11B2 (2,216.4 [1,112.0, 2,813.5]-fold, p < 0.001), MC2R (2.88 [2.00, 4.52]-fold, p < 0.001), and AGTR1 (1.80 [1.02, 2.80]-fold, p < 0.001]), and lower transcript levels of MRAP, CYP17A1, and CYP11B1 (0.28–0.36, p < 0.001 for all). MC2R and CYP11B2 transcripts were lower in APAs with KCNJ5 vs. other mutations (p < 0.01 for both). MC2R expression correlated positively with that of AGTR1 in APAs harboring KCNJ5 and CACNA1D mutations, and with MRAP expression in APAs harboring ATPase mutations. Conclusions While MC2R and AGTR1 are expressed in all APAs, differences were observed based on the underlying aldosterone-driver somatic mutations. In tandem, our findings suggest that APAs with ATPase-mutations are more responsive to ACTH than KCNJ5-mutated APAs.